a) Ta có: x + 34 là bội của x + 1
=> x + 34 \(⋮\)x + 1
=> (x + 1) + 33 \(⋮\)x + 1
=> 33 \(⋮\)x + 1
=> x + 1 \(\in\)Ư(33) = {1; 3; 11; 33}
Với: x + 1 = 1 => x = 1 - 1 = 0
x + 1 = 3 => x = 3 - 1 = 2
x + 1 = 11 => x = 11 - 1 = 10
x + 1 = 33 => x = 33 - 1 = 32
b) HD: 2x + 1 là ước của 4x + 82
=> 4x + 82 là B(2x + 1)
=> 2(2x + 1) + 80 \(⋮\)2x + 1
=> 80 \(⋮\)2x + 1 => 2x + 1 \(\in\)Ư(80) = {...} (tự liệt kê)
còn lại TT câu a
c) cx như trên
d) Ta có: 3x + 6 \(⋮\)2x - 1
=> 2(3x + 6) \(⋮\)2x - 1
=> 6x + 12 \(⋮\)2x - 1
=> 3(2x - 1) + 15 \(⋮\)2x - 1
=> 15 \(⋮\)2x - 1 => 2x - 1 \(\in\)Ư(15) = {1; 3; 5; 15}
còn lại tự lm (như trên)